Scandinavian Legal Realism and Human Rights: Axel Hägerström, Alf Ross and the Persistent Attack on Natural Law. Issue 3 (3rd July 2018) - Strang, Johan
ABSTRACT: Scandinavian Legal Realism occupies a controversial space in Nordic historiography. Some celebrate it as the legal philosophy of the democratic and egalitarian Nordic welfare state; others scorn it for having contributed to a state-apologetic and rights-sceptical Nordic political culture that prioritised the common good over individual human rights. This article is motivated by an impression that a certain historical sensitivity is lacking from this discussion. Focusing on the Swedish philosopher Axel Hägerström and the Danish legal theorist Alf Ross, the article explores what the legal realists actually said about human rights and reconstructs the context and purpose of their criticism. How did they envision international law, democracy or the welfare state without human rights? How was it possible to continue the crusade against natural law after the Second World War? And is there anything to be learned from their criticism at a time when we in the Nordic countries, as elsewhere, are asking ourselves many of the same fundamental questions regarding the relation between law and politics as well as the universality of human rights?